Structure and Properties of Prussian Blue Analogues in Energy Storage and Conversion Applications. (9th October 2020) - Yi, Haocong; Qin, Runzhi; Ding, Shouxiang; Wang, Yuetao; Li, Shunning; Zhao, Qinghe; Pan, Feng
Abstract: In recent years, Prussian blue analogue (PBA) materials have been widely explored and investigated in energy storage/conversion fields. Herein, the structure/property correlations of PBA materials as host frameworks for various charge‐carrier ions (e.g., Na +, K +, Zn 2+, Mg 2+, Ca 2+, and Al 3+ ) is reviewed, and the optimization strategies to achieve advanced performance of PBA electrodes are highlighted. Prospects for further applications of PBA materials in proton, ammonium‐ion, and multivalent‐ion batteries are summarized, with extra attention given to the selection of anode materials and electrolytes for practical implementation. This work provides a comprehensive understanding of PBA materials, and will serve as a guidance for future research and development of PBA electrodes. Abstract : This work reviews the structure/property correlations of Prussian blue analogue (PBA) materials as host frameworks for various charge‐carrier ions (e.g., Na +, K +, Zn 2+, Mg 2+, Ca 2+, and Al 3+ ), highlights the optimization strategies to achieve advanced performance of PBA electrodes, summarizes and proposes the further research and applications of PBA materials in electrochemical energy storage/conversion fields.